Planning the Implementation of a 3R (Reduce, Reuse, and Recycle) Waste Management Facility for the Prevention of Waste-Related Diseases in Sukawening Village, Bandung Regency - Allan Darma Putra Pramudita; Melbi Tanjung; Sri Ratna Wulan; Muhammad Anang Hadiat; Riska Septiana; Dita Septiani (Society : Jurnal Pengabdian Masyarakat, 2026)
Waste generation in Sukawening Village has exceeded the capacity of the existing 3R (Reduce, Reuse, and Recycle) temporary waste management facility (TPS 3R), while current waste treatment practices still rely on open burning. Therefore, it is necessary to develop a plan for a TPS 3R facility capable of accommodating all household waste and reducing waste generation without the use of burning in Sukawening Village.The community service methodology employed in this study includes educational seminars on waste management, the promotion of a healthy environmental culture, and practical training on household-scale composting. In addition, a quantitative approach was applied to develop a feasible TPS 3R planning framework for Sukawening Village. The outcomes of this community service activity are expected to promote more environmentally friendly behavior among the community, enable households to reduce waste generation through composting practices, and provide a viable plan for the development of a TPS 3R facility in Sukawening Village.